Towards a supportive math pedagogy: Power dynamics and academic integrity considerations - Yusun, Timothy; Gagné, Ann (Canadian Perspectives on Academic Integrity, 2021)
Mathematics is a discipline with implicit power dynamics that affects who is seen as a viable educator and learner. In this paper we explore the power dynamics of the teaching and learning of mathematics at the university level, highlighting the inequitable and exclusionary aspects of math pedagogy that can lead to academic misconduct. We argue that a supportive pedagogy that meets learners at their social location will model academic integrity and create an educational environment that is inclusive of diverse learners. The potential effect of a supportive pedagogy that keeps universal design in mind, means a reconceptualization of both learning outcomes as well as surveilled high-stakes assessments for traditionally exclusionary fields such as mathematics.